Social network analysis of B2B networks - Mohamad, Abdul Hadi; Fang, Wang; Abu Bakar, Noor Widasuria; Jatavallabhula, Pavan Kumar (2017)
The volume of information readily available in the EMarketplace is massive.Business-to-business (B2B) users, for instance, have an extensive chain of business relationships that have immensely generated a large volume of information. Although this raises problems of information overload, the data is embedded with rich and valuable information, such as internal structure and social networks.While other research focuses on discovering properties of B2C, C2C and P2P networks, there only exists limited work on B2B, attributable to the high complexity of the B2B structure.This paper presents a statistical analysis of B2B networks that amasses dispersed users' social relationships using a social network analysis technique.The investigation performed found that B2B networks are small-world, and thus follow a power-law distribution. The analysis also proved that B2B networks hold stable community structures.